PENGELOLAAN INFRASTRUKTUR BUS TRANS METRO PEKANBARU OLEH DINAS PERHUBUNGAN KOTA PEKANBARU - Roza Erlina; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Management Infrastructure of Trans Metro bus is a method implemented by the Transportation Department of Pekanbaru City to make Trans Metro Kota Pekanbaru a safe comfortable, reliable and affordable and made pekanbaru livable as a city. Transmetro management is in control The department of transportation Pekanbaru managed by technical service unit of of urban transportation management system. The purpose of this study is to find out how management Infrastrukture of Trans Metro bus and inhibiting factors . Is the theoretical concept used by the writers is management function by Amirullah  which consists of:Planning, Organization, actuating, controlling. The research method used is a type of qualitative research case study approach, the selection of informants using the purposive sampling technique. The techniques of collecting data are through observation, interviews, library studies, and documentation. The results of this study at  realization Strategic the management of Trans Metro bus by Departement Transportation at Pekanbaru city optimally. The inhibiting factors include facilities and infrastructure , budget , human resources and lack of public awareness . It’s better if The department of transportation Pekanbaru does The management of transpotation Trans Metro Pekanbaru well and solving the traffic problems, air polution in order to Transportation Trans Metro can operate in pekanbaru and made sustainable transport. Keywords: Management, Infrastructure, Trans Metro Pekanbaru